Solution:
[tex]\frac{1}{5} x+\frac{1}{4}=\frac{1}{2}(x+5)\\\frac{1}{5} x+\frac{1}{4}=(\frac{1}{2})(x)+(\frac{1}{2})(5)\\\frac{1}{5} x+\frac{1}{4}=\frac{1}{2}x+2\frac{1}{2} \\\frac{1}{5} x - \frac{1}{5} x +\frac{1}{4} - 2\frac{1}{2}=\frac{1}{2}x+2\frac{1}{2} - 2\frac{1}{2} - \frac{1}{5} x\\\frac{1}{4}-2\frac{1}{2} = \frac{1}{2}x-\frac{1}{5}x\\-2\frac{1}{4}=\frac{3}{10}x\\-2\frac{1}{4}* \frac{10}{3}=\frac{3}{10}x * \frac{10}{3}\\-\frac{15}{2}= x\\-7.5=x[/tex]
Answer:
[tex]x=-7.5[/tex]
Check:
[tex]\frac{1}{5}(-7.5)+\frac{1}{4}=\frac{1}{2}[(-7.5)+5] \\-\frac{3}{2} +\frac{1}{4}=\frac{1}{2}(-2.5)\\-\frac{5}{4} = -\frac{5}{4}[/tex]
Hope this was helpful.